A Principled Pedagogy for Religious Educators - Evans, David (Religious education, 2017)
Drawing on whiteness literature and over fifty years of combined classroom instruction experience, two professors of race and religion-one black, one white-at predominantly white institutions, answer the question, "How do we as religious educators effectively teach white students to challenge racially distorted assumptions and promote racially just outcomes?" In reply, they call into question the idea of "safe space," dissect "the white gaze," and offer three pedagogical principles for preparing white students to be allies in antiracist struggle: principled dislocation, supportive relocation, and sustained cultivation.